2022
DOI: 10.3897/evolsyst.6.87670
|View full text |Cite
|
Sign up to set email alerts
|

Cercarial dermatitis outbreak caused by ruminant parasite with intermediate snail host: schistosome in Chana, South Thailand

Abstract: A cercarial dermatitis outbreak occurred in Chana district, Songkhla Province, South Thailand, between August and October 2020. A total of 359 cases with cercarial dermatitis were confirmed with three cases of skin biopsy. The species of potential trematodes from infected snails were investigated, and the prevalence of infestation with schistosomes was described. As part of our ongoing studies of trematode diversity in freshwater systems, using morphological traits and sequence data to differentiate species, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
2
9
1
Order By: Relevance
“…We observed two morphological types of trematode cercariae: Furcocercous and Echinostome. Our observed rate of cercarial infection in I. exustus was higher than that previously recorded in Thailand (2.05%–5.5%) [ 30 , 31 ] and neighboring countries such as Malaysia (1.7%) [ 32 ] and Vietnam (38.5%) [ 33 ]. The diversity of trematode larvae in I. exustus was quantified.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…We observed two morphological types of trematode cercariae: Furcocercous and Echinostome. Our observed rate of cercarial infection in I. exustus was higher than that previously recorded in Thailand (2.05%–5.5%) [ 30 , 31 ] and neighboring countries such as Malaysia (1.7%) [ 32 ] and Vietnam (38.5%) [ 33 ]. The diversity of trematode larvae in I. exustus was quantified.…”
Section: Discussioncontrasting
confidence: 78%
“…In a recent study, Krailas et al . [ 31 ] reported that I. exustus from Chana, Southern Thailand, were infected with three types of cercariae: S. indicum , Echinostoma spiniferum , and Clinostomum giganticum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, I. exustus is widely distributed in Asia, Africa, and the Caribbean region [1][2][3][4]. This organism has been reported as an intermediate host for various trematode parasites (Trematoda: Digenea) in veterinary and medical fields [5,6]. I. exustus is known as the intermediate host for Schistosoma indicum, S. nasale, and S. spindale, as well as other trematodes such as Clinostomum giganticum and Echinostoma spp.…”
Section: Introductionmentioning
confidence: 99%
“…I. exustus is known as the intermediate host for Schistosoma indicum, S. nasale, and S. spindale, as well as other trematodes such as Clinostomum giganticum and Echinostoma spp. [5,6]. Moreover, I. exustus has been reported in association with outbreaks of cercarial dermatitis in humans in Thailand, Malaysia, Laos, and India [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%